Carbon-based nanocomposite decorated with bioactive glass and CoNi2S4 nanoparticles with potential for bone tissue engineering - Mojtaba Bagherzadeh; Abdullah Aldhaher; Sepideh Ahmadi; Nafiseh Baheiraei; Navid Rabiee (Elsevier, 2022)
In this work, for the first time, different forms of nanocomposites based on rGO and MWCNT were prepared in conjoining with the bioactive glass (BioGlass). In the carbonic layers, a highly toxic nanoparticle, CoNi2S4, was intercalated, and the role of this nanoparticle in the alkaline phosphatase activity, relative cell viability on different cell lines, and also the effect on the cell walls and cell morphologies were investigated. From another perspective, the ability of the chemotherapy drug loading to the prepared nanocomposites was investigated, and the use of leaf extracts was thought of as a green method to lower the cytotoxicity and regulate the genotoxicity of the generated nanocomposite. The results showed that the nanocomposites without the chemotherapy drug had higher relative cell viability than the drug-loaded nanocomposites. The relative cell viability also reached a new range when the leaf extract was applied to the surface. Thus, utilizing a leaf extract to raise the relative cell viability would be considered a novel and unique technique. From another perspective, the ALP activity of the nanocomposites, along with the toxic nanoparticles, showed promising results with the appropriate cell-seeded factors. In this regard, the morphology of the cells and the nanocomposites after seeding and treatment with each other on the hBMSCs and HEK-293 cell lines were investigated. The findings demonstrated that the shape of the nanocomposites has significantly changed in morphology as a result of the cell wall degradations and aggregations; the treated HEK-293 cell line's morphology, however, shows no significant changes after 4 h.